Modernism, Media, and Propaganda : British Narrative from 1900 to 1945 - Wollaeger, Mark (Princeton University Press, 2008)
Though often defined as having opposite aims, means, and effects, modernism and modern propaganda developed at the same time and influenced each other in surprising ways. The professional propagandist emerged as one kind of information specialist, the modernist writer as another. Britain was particularly important to this double history. By secretly hiring well-known writers and intellectuals to write for the government and by exploiting their control of new global information systems, the British in World War I invented a new template for the manipulation of information that remains with us to this day. Making a persuasive case for the importance of understanding modernism in the context of the history of modern propaganda, Modernism, Media, and Propaganda also helps explain the origins of today's highly propagandized world. Modernism, Media, and Propaganda integrates new archival research with fresh interpretations of British fiction and film to provide a comprehensive cultural history of the relationship between modernism and propaganda in Britain during the first half of the twentieth century. From works by Joseph Conrad to propaganda films by Alfred Hitchcock and Orson Welles, Mark Wollaeger traces the transition from literary to cinematic propaganda while offering compelling close readings of major fiction by Virginia Woolf, Ford Madox Ford, and James Joyce.